A Dynein-dependent shortcut rapidly delivers axis determination transcripts into theDrosophilaoocyte - Alejandra Clark; Carine Meignin; Ilan Davis (2007)
The primary axes of Drosophila are set up by the localization of transcripts within the oocyte. These mRNAs originate in the nurse cells, but how they move into the oocyte remains poorly understood. Here, we study the path and mechanism of movement of gurken RNA within the nurse cells and towards and through ring canals connecting them to the oocyte. gurken transcripts, but not control transcripts, recruit the cytoplasmic Dynein-associated co-factors Bicaudal D (BicD) and Egalitarian in the nurse cells. gurken RNA requires BicD and Dynein for its transport towards the ring canals, where it accumulates before moving into the oocyte. Our results suggest that bicoid and oskar transcripts are also delivered to the oocyte by the same mechanism, which is distinct from cytoplasmic flow. We propose that Dynein-mediated transport of specific RNAs along specialized networks of microtubules increases the efficiency of their delivery, over the flow of general cytoplasmic components, into the oocyte.